2013
DOI: 10.1089/thy.2012.0378
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Elevation of Serum Thyrotropin Levels in Patients Treated with Axitinib

Abstract: This is the first study to report an inappropriate elevation of serum TSH levels in patients treated with axitinib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Thyroid dysfunction in TKI treatment is a commonly recognized AE. Axitinib, pazopanib, sorafenib, sunitinib, and lenvatinib have been reported to cause thyroid-related AEs [5,6,[13][14][15]. Lenvatinib has been used for thyroid cancer and thyroidectomy; however, reports of AEs of thyroid dysfunction are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid dysfunction in TKI treatment is a commonly recognized AE. Axitinib, pazopanib, sorafenib, sunitinib, and lenvatinib have been reported to cause thyroid-related AEs [5,6,[13][14][15]. Lenvatinib has been used for thyroid cancer and thyroidectomy; however, reports of AEs of thyroid dysfunction are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence suggests an impairment in deiodases activity in TKIinduced hypothyroidism. Indeed, in this condition, TSH levels are often inappropriately high for the concomitant serum free T3 and free T4 levels (194,207). This might be related to a far more reduced activity of DIO2 (expressed in the pituitary gland) than of deiodinase-1 (expressed mainly in the liver and kidney), leading to an intracellular depletion of T3 in the thyrotrophs and an inappropriately high TSH level (194).…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…From an oncological viewpoint, the fact that Graves’ disease occurred after two different TKIs suggests that it could be a rare but important class effect. As several studies have also demonstrated impaired thyroid function with sunitinib [10–14], axitinib [15, 16] and motesanib [17], our case report emphasizes the need for thyroid follow-up during any treatment with a TKI in order to screen for both hypothyroidism and hyperthyroidism. Systematically measuring anti-TSH receptor antibodies before TKI initiation is not realistic due to the low frequency of hyperthyroidism, unlike with hypothyroidism.…”
Section: Resultsmentioning
confidence: 68%